Analisis Kadar Nikotin dan Identifikasi Senyawa Bioaktif pada Ekstrak Daun Tembakau Asal Gayo (Nicotiana tabacum L.) Menggunakan GC–MS dan Titrasi - Intan Sabila Putri Purba; Supiyani Supiyani; Haris munandar Nasution; Minda Sari Lubis (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Gayo-origin tobacco leaves (Nicotiana tabacum L.) are a locally cultivated tobacco variety widely grown in Central Aceh, Indonesia. Tobacco leaves are known to contain nicotine, a bioactive compound with various pharmacological and economic potentials. This study aimed to identify the nicotine content and phytochemical profile of Gayo tobacco leaf extract. The research procedures included sample collection, macroscopic and microscopic examinations, simplicia preparation, characterization of the simplicia and extract, phytochemical screening, quantitative nicotine determination using acidimetry titration, and qualitative analysis using Gas Chromatography–Mass Spectrometry (GC–MS). Macroscopic examination showed that the leaves were oval to round in shape, broad-surfaced, green in color, with a characteristic odor and a bitter taste. Microscopic observation revealed the presence of vascular bundles, covering trichomes, and glandular hairs in the leaf fragments. The titrimetric test showed nicotine levels of 0.95 ± 0.3% in the simplicia powder and 1.87 ± 0.45% in the ethanol extract. GC–MS analysis identified several major compounds, including nicotine (20.99%) and Labda-8(20),13-dien-15-oic acid (29.85%) as dominant components, along with minor compounds such as Quinolin, 8-amino-6-hydroxy-Quinazoline (2.39%). These findings indicate that the Gayo tobacco leaf extract contains a relatively high level of nicotine and is dominated by alkaloid and diterpenoid acid derivatives, suggesting its potential for further phytochemical and pharmacological exploration.